PARKING - A PROBLEM OF MODERNE TOWNS - Kalasova, Alica (Doprava a spoje, 2009)
Traffic moderation in cities is a process that reflects the pursuit for a new quality of life as well as applying modern transport policies at European level. In practice, there are many different types of this process depending on the type of area, road and citizens' requirements. Parking policy represents a compromise between free mobility, accessibility and life quality. This is the reason why parking should be involved in urban policy connected with mobility and accessibility.